Invasive Alien Species: Silent Threats to the OUVs of Natural World Heritage Sites in South Asia - Hazarika, Panchali; Nath, Anukul; Talukdar, Gautam (Indian Forester, 2025)
The lUCN World Heritage Outlook identifies invasive alien species (IAS) as one of the most significant threats to natural World Heritage sites. The World Heritage Committee (WHC) considers invasive species to be "threat multipliers" for natural heritage sites. This study’s literature review focuses on scientific contributions that highlight the impact of biological invasions in the Natural World Heritage Sites (NWHS) of South Asia. Species such as Mikania micrantha, Mimosa spp., and Chromolaena (Eupatorium) odorata have been reported to have caused devastation in large areas of grasslands and floodplains, severely impacting the habitat of endemic one-homed rhinoceros and other herbivores. In protected waters of India and Sri Lanka, the introduction of non-native fish species has led to declines in endemic fish and crustacean populations, thus disrupting the native biodiversity. Heritage site management authorities have responded by developing strategies to combat these persistent invasions, encouraging local communities to join the efforts. Global organizations such as lUCN and UNESCO WHC have urged governments to Implement targeted actions to address IAS and protect the biodiversity of NWHS. However, comprehensive management plans are still needed to effecttveiy tackle this growing threat in affected natural heritage areas.